FUNGAL CELLULASE; PRODUCTION AND APPLICATIONS: MINIREVIEW - Ahmed, Amer; Bibi, Aasia (LIFE: International Journal of Health and Life-Sciences, 2018)
Cellulose is the most abundant biomaterial derived from the living organisms on the earth; plant is the major contributor to the cellulose pool present in the biosphere. Cellulose is used in variety of applications ranging from nanomaterials to biofuel production. For biofuel production, cellulose has first to be broken-down into its building blocks; β-D-glucosyl unit which subsequently can be fermented to different product such as ethanol, acetic acids, among others. Cellulase is the enzymatic system, which degrades cellulose chains to glucose monomers. Cellulase is a group of three enzymes endoglucanase, exoglucanases and β-glucosidases which act together to hydrolyze cellulose to glucose units. Cellulases are found in bacteria, fungi, plants, and some animals. Fungi are the preferred source of cellulase for industrial applications since they secrete large quantities of cellulase to culture medium. Despite a remarkable number of fungi found to produce cellulase enzymes, few have been extensively investigated because they produce large quantities of these enzymes extracellularly. In this mini-review, the production of cellulase from fungi and the parameters affecting cellulase production are discussed briefly on light of recent publications. Furthermore, potential applications of cellulase enzymes are highlighted.